2017
DOI: 10.1016/j.mjafi.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A clinical correlation of conjunctival microangiopathy with grades of retinopathy in type 2 diabetes mellitus

Abstract: A positive correlation was seen between conjunctival vessel width and tortuosity with severity of retinopathy. Widths over 80 μ and tortuous segment length over 900 μ are suggestive of severe grades of retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Cheung et al 7 used CAIM and found that microvascular abnormality severity index was associated with HbA1c levels in T1DM. Based on previous studies 13 , 15 , 23 , 25 , 26 , impairment of vascular barrier function and deposition of hemosiderin resulted in abnormal perivascular color. Changes in the conjunctival vessels of diabetes patients include thickening of vascular wall, abnormal perivascular color, morphological distortion, microaneurysms, abnormal A/V ratio, slower blood flow, etc., which are generally difficult to be detected by eyes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Cheung et al 7 used CAIM and found that microvascular abnormality severity index was associated with HbA1c levels in T1DM. Based on previous studies 13 , 15 , 23 , 25 , 26 , impairment of vascular barrier function and deposition of hemosiderin resulted in abnormal perivascular color. Changes in the conjunctival vessels of diabetes patients include thickening of vascular wall, abnormal perivascular color, morphological distortion, microaneurysms, abnormal A/V ratio, slower blood flow, etc., which are generally difficult to be detected by eyes.…”
Section: Discussionmentioning
confidence: 87%
“…Early detection is crucial for decreasing the risk of disease progression and improving prognosis. Previous studies have found that conjunctival abnormalities occur earlier than retinal abnormalities in patients with diabetes 14 , 23 . This has been further confirmed by the current study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to WHO statistics, mortality from vascular complications has increased from 21.2% to 77% over the past 90 years [17]. Medico-social problem of DM is caused by early disability and mortality of patients due to specifi c complications, such as microangiopathy (nephropathy, retinopathy), macroangiopathy (myocardial infarction, stroke, gangrene of the lower extremities), neuropathy, as well as sexual dysfunction [1,7]. Hyperglycemia leads to oxidative stress and the formation of reactive oxygen species, which can cause decreased testosterone levels, changes in the structure of the seminal tubules, impaired spermatogenesis which can lead to male infertility [10,18].…”
Section: Age Peculiarities Of Morphological Changes Of Vessels Of Testicular Hemomicrocirculatory Flow In Streptozotocin Diabetes Mellitumentioning
confidence: 99%
“…Diabetes mellitus (DM) causes great socio-economic damage, which is determined by medical expenses and expenditure on social security to patients due to invalidity and loss of labour capacity [1,2]. More than 1 million patients with DM are registered in Ukraine, but the actual number of people with undiagnosed pathology exceeds this figure by 3-4 times [3].…”
mentioning
confidence: 99%